Erythropoietic response to oral iron in patients with nondialysis-dependent chronic kidney disease in the FIND-CKD trial? - Macdougall, Iain C.; Bock, Andreas H.; Carrera, Fernando; Eckardt, Kai-Uwe; Gaillard, Carlo; Van Wyck, David; Meier, Yvonne; Larroque, Sylvain; Perrin, Amandine; Roger, Simon D. (Clinical Nephrology, 2017)
To evaluate erythropoietic response rates to oral iron over time in iron-deficient anemic patients with nondialysis-dependent chronic kidney disease (ND-CKD).FIND-CKD was a 1-year, randomized, multicenter trial of iron therapy in patients with ND-CKD, anemia, and iron deficiency, without erythropoiesis-stimulating agent (ESA) therapy. Patients with active infection or C-reactive protein > 20 mg/L were excluded. In this post-hoc analysis, response was defined as >= 1 g/dL increase in hemoglobin (Hb) from baseline, before initiation of alternative anemia therapy (i.e., ESA, transfusion, or intravenous iron).308 patients received oral iron (200 mg elemental iron/day). Mean (SD) Hb at baseline was 10.4 (0.7) g/dL. At week 4, Hb data were available from 292 patients without alternative anemia therapy: 63/292 (21.6%) showed a response. Among the 229 nonresponders at week 4, 48.8% showed a cumulative response on >= 1 occasion by week 52 (11.1%, 19.9%, 25.9%, and 28.7% had a response at weeks 8, 12, 24, and 52, respectively), and 27.9% had received alternative iron therapy by week 52. Baseline levels of Hb, ferritin, and transferrin saturation were lower in responders than in nonresponders. Neither concomitant medication nor adherence (as assessed by medication count) was substantially different between early responders and nonresponders.Four weeks after starting oral iron therapy, only 21.6% of anemic patients with ND-CKD and iron deficiency showed an Hb increase of at least 1 g/dL. Among early nonresponders, < 30% responded at any subsequent time point. Earlier consideration of alternative therapy could improve anemia management in this population.?.
EVALuna:34854